Implementing Task-Based Language Teaching to Integrate Language Skills in an EFL Program at a Colombian University - Eulices Córdoba Zúñiga (Universidad Nacional de Colombia, 2016)
This article reports the findings of a qualitative research study conducted with six first semester students of an English as a foreign language program in a public university in Colombia. The aim of the study was to implement task-based language teaching as a way to integrate language skills and help learners to improve their communicative competence in English. The results suggest that the implementation of task-based language teaching facilitated the integration of the four skills in the English as a foreign language context. Furthermore, tasks were meaningful and integrated different reading, writing, listening, and speaking exercises that enhanced students' communicative competences and interaction. It can be concluded that task-based language teaching is a good approach to be used in the promotion of skills integration and language competences.